The Ziswaf fund as a potential capital source for educational development in Malaysia / Azizah Daut ...[et al.] - Daut, Azizah; Che Yaacob, Ahmad; Mohd Don, Mohd Ali; Ismail, Normah; Mohamed, Safiah (2013)
Purpose - This is a concept paper that explores the prospect of establishing a model for the zakah, waqf, and infaq (ZISWAF) fund as a potential capital source for educational development in Malaysia. Methodology - The exploration is done through a content analysis of the selected models of waqf funds and observations that were carried out during research visits to several establishments like Majlis Ugama Islam Singapura (MUIS) Dompet Dhuafa Indonesia, and Majlis Agama Islam Johor (MAIJ) Finding - This study found that a number of institutions in Malaysia, Singapore and Indonesia have already adopted the mechanisms of Zakah, waqf, and infaq that can be emulated and can eventually serve as a contemporary model for distributing philanthropic funds. Implication - A social fundraising mechanism for the significant purpose of education can be modeled after prominent educational institution such as the Harvard University Endowment that has accumulate assets of more than USD 32 billion.